Acceleration the drying process of oleaster (Elaeagnus angustifolia L.) using reflectors and desiccant system in a solar drying system. (June 2021) - Rashidi, Milad; Arabhosseini, Akbar; Samimi-Akhijahani, Hadi; Kermani, Ali M.
Abstract: In present work, a flat plate collector assisted with reflecting system and desiccant wheel was used to dry oleaster fruit ( Elaeagnus angustifolia L. ). Three levels of air flow rate (0.025, 0.05 and 0.09 kg/s) and different dryer conditions: with reflectors (WR), with reflectors and desiccant wheel (WRD) and without reflectors and desiccant wheel (WORD) were considered to dry single layer of oleaster. The results indicated that the effect of using reflectors and desiccant system on extraction moisture from product was significant (P < 0.05). By using reflectors and desiccant wheel, the specific energy consumption for drying oleaster was decreased by 11.32–30.15%. The overall efficiency for WRD was obtained in the range of 33.21–39.64% which was higher than the system without reflectors and desiccant system. The results of the exergetic analysis showed that maximum exergy efficiency of drying system for WR, WRD and WORD was 38.8%, 56.7% and 32.1%, respectively. Solar thermal fraction rate for WRD was lower due to higher thermal energy inside of the drying cabinet. The payback time for system with optimized condition can be decreased about 15%. The quality consideration showed that the quality of oleaster (also the powder) dried by WRD is better than WORD and sun drying samples. Highlights: Drying kinetics of oleaster studied by a solar dryer with reflectors and desiccant. Using reflectors and desiccant system accelerates the drying process of the samples. A minimum value of specific energy consumption was achieved. The exergetic analysis of drying cabinet and drying process was carried out. Based on the initial condition economic optimization of collector was developed.